2018
DOI: 10.5539/ijef.v10n7p78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Participation of Micro and Small Enterprises in Microfinance on Their Performance in Kenya

Abstract: The development of the microfinance sub-sector in Kenya is seen as a favourable catalyst for increasing performance of Micro and Small Enterprises (MSEs). Despite the development, MSEs continue to suffer from high levels of financial exclusion and shortage of operating funds. This scenarios raise policy questions on whether participation in microfinance has effects on performance of MSEs. While past studies on this relationship have demonstrated that the effects are mixed, an understanding of the effects on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
2
1
2
Order By: Relevance
“…This is because many who took loans did not use the funds to expand their businesses but rather used them for other purposes like paying school fees for their children, spending on household needs, and settling medical bills among other things. This result was contrary to that of Kiriti et al (2008), Oketch (1999), Obebo et al (2018) andMacharia (2003) who found a positive relationship between credit utilization and performance of enterprises. In their studies, the credit was used for the intended purpose of being capital for the business.…”
Section: Regression Resultscontrasting
confidence: 91%
“…This is because many who took loans did not use the funds to expand their businesses but rather used them for other purposes like paying school fees for their children, spending on household needs, and settling medical bills among other things. This result was contrary to that of Kiriti et al (2008), Oketch (1999), Obebo et al (2018) andMacharia (2003) who found a positive relationship between credit utilization and performance of enterprises. In their studies, the credit was used for the intended purpose of being capital for the business.…”
Section: Regression Resultscontrasting
confidence: 91%
“…Microfinance may significantly influence the success of SMEs. Obebo et al (2018) used a crosssectional survey to determine if small enterprises failed due to the financial exclusion or limited loan capabilities due to shortages in operating funds. The authors examined data collected from the 2016 FinAccess Dataset and observed the abilities and risks from owners of small enterprises.…”
Section: Importance Of Microloans For Small Business Ownersmentioning
confidence: 99%
“…Dalam konteks bisnis, biaya adalah segala hal yang dikeluarkan dalam rangka menghasilkan output dalam skala tertentu (Obebo, Wawiwe& Muniu, 2018). Biaya produksi merupakan semua beban yang harus dikeluarkan oleh produsen dalam rangka menghasilkan suatu barang/produksi.…”
Section: Konsep Biayaunclassified
“…Dengan skala permodalan yang meningkat, maka kegiatan produktif dari pelaku usaha juga meningkat, contohnya kemampuan produksi, pemasaran, dan penciptaan inovasi. Obebo, Wawiwe& Muniu (2018) menemukan bahwa selama pelaku usaha meningkatkan kualitas permodalan, maka kegiatan usaha dapat mencapai keunggulan kompetitif lebih besar dan kinerja bisnis lebih tinggi. Keunggulan kompetitif mampu meningkatkan omset penjualan karena produk dan nilai tambah produk/jasa mampu menguasai pangsa pasar.…”
Section: Diskusi Pembahasan a Pengaruh Modal Terhadap Tingkat Pendapunclassified